Genotyping Reveals High Clonal Diversity and Widespread Genotypes of Candida Causing Candidemia at Distant Geographical Areas - Guinea, Jesús; Arendrup, Maiken C.; Cantón, Rafael; Cantón, Emilia; García-Rodríguez, Julio; Gómez, Ana; de la Pedrosa, Elia Gómez G.; Hare, Rasmus K.; Orden, Beatriz; Sanguinetti, Maurizio; Pemán, Javier; Posteraro, Brunella; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
The objectives of this study were to gain further insight on Candida genotype distribution and percentage of clustered isolates between hospitals and to identify potential clusters involving different hospitals and cities. We aim to genotype Candida spp. isolates causing candidemia in patients admitted to 16 hospitals in Spain, Italy, Denmark, and Brazil. Eight hundred and eighty-four isolates (Candida albicans, n=534; C. parapsilosis, n=282; and C. tropicalis, n=68) were genotyped using species-specific microsatellite markers. CDC3, EF3, HIS3, CAI, CAIII, and CAVI were used for C. albicans, Ctrm1, Ctrm10, Ctrm12, Ctrm21, Ctrm24 and Ctrm28 for C. tropicalis, and CP1, CP4a, CP6, and B for C. parapsilosis. Genotypes were classified as singletons (genotype only found once) or clusters (same genotype infecting two or more patients). Clusters were defined as intra-hospital (involving patients admitted to a single hospital), intra-ward (involving patients admitted to the same hospital ward) or widespread (involving patients admitted to different hospitals). The percentage of clusters and the proportion of patients involved in clusters among species, genotypic diversity and distribution of genetic diversity were assessed. Seven hundred and twenty-three genotypes were detected, 78 (11%) being clusters, most of which (57.7%; n=45/78) were intra-hospital clusters including intra-ward ones (42.2%; n=19/45). The proportion of clusters was not statistically different between species, but the percentage of patients in clusters varied among hospitals. A number of genotypes (7.2%; 52/723) were widespread (found at different hospitals), comprising 66.7% (52/78) of clusters, and involved patients at hospitals in the same city (n=21) or in different cities (n=31). Only one C. parapsilosis cluster was a widespread genotype found in all four countries. Around 11% of C. albicans and C. parapsilosis isolates causing candidemia are clusters that may result from patient-to-patient transmission, widespread genotypes commonly found in unrelated patients, or insufficient microsatellite typing genetic discrimination.